The Influence of Service Quality and Brand Equity on Attitude and Behavior Loyalty on Bank Jatim Syariah Surabaya Branch - Nurul Kamaril; Nurul Aini; Joko Suyono; Damarsari Ratnasahara (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This paper aims to analyze the influence of service quality and brand equity on attitude and behavior loyalty in the customers from Bank Jatim Syariah Surabaya. Design/methodology/approach: The method used is statistic-descriptive and the design used is cross sectional. Findings: 2 out of 7 hypotheses are accepted while the other 5 is rejected. Research limitations/implications: Variables considered in this study are service quality, brand equity, attitude loyalty, and behavior loyalty. The samples are 80 respondents from Bank Jatim Syariah Surabaya that were chosen using purposive sampling. Practical implications: Results show that from the 7 hypotheses proposed, only 2 that are accepted. Originality/value: This paper is original. Paper type: This paper can be categorized as a case study.